PrPC from stem cells to cancer - Martin-Lannerée, Séverine; Hirsch, Théo Z.; Hernandez-Rapp, Julia; Halliez, Sophie; Vilotte, Jean-Luc; Launay, Jean-Marie; Mouillet-Richard, Sophie (Frontiers in Cell and Developmental Biology, 2014)
The cellular prion protein PrPC was initially discovered as the normal counterpart of the pathological scrapie prion protein PrPSc, the main component of the infectious agent of Transmissible Spongiform Encephalopathies. While clues as to the physiological function of this ubiquitous protein were greatly anticipated from the development of knock-out animals, PrP-null mice turned out to be viable and to develop without major phenotypic abnormalities. Notwithstanding, the discovery that hematopoietic stem cells from PrP-null mice have impaired long-term repopulating potential has set the stage for investigating into the role of PrPC in stem cell biology. A wealth of data have now exemplified that PrPC is expressed in distinct types of stem cells and regulates their self-renewal as well as their differentiation potential. A role for PrPC in the fate restriction of embryonic stem cells has further been proposed. Paralleling these observations, an overexpression of PrPC has been documented in various types of tumours. In line with the contribution of PrPC to stemness and to the proliferation of cancer cells, PrPC was recently found to be enriched in subpopulations of tumour-initiating cells. In the present review, we summarize the current knowledge of the role played by PrPC in stem cell biology and discuss how the subversion of its function may contribute to cancer progression.